INOVASI ECO ENZYME SEBAGAI SOLUSI RAMAH LINGKUNGAN DI NAGARI LASI KECAMATAN CANDUANG KABUPATEN AGAM - Syaifuddin Islami; Dewi Anggraini; Dedet Deperiky (LPPM Universitas Andalas, 2023)
Agriculture plays a crucial role in meeting food needs and improving the well-being of communities. However, challenges to the sustainability and productivity of agriculture are on the rise. Dependency on chemical fertilizers and synthetic pesticides has had negative environmental impacts. Eco enzymes, as an innovative organic fertilizer, offer a sustainable solution. Eco enzymes enhance soil productivity and quality while reducing reliance on synthetic chemicals. This project was conducted in Nagari Lasi, Canduang District, Agam Regency, from October 2022 to May 2023. The method involved the participation of farmers and the local community in every stage of the project to facilitate knowledge transfer and broader adoption of the innovation. The results of this project introduced the innovation to farmers and the community through various demonstration activities. The aim is to provide a comprehensive understanding of sustainable agriculture revitalization through eco enzymes. Eco enzymes for agriculture can improve nutrient absorption efficiency by plants, reduce environmental pollution potential, and enhance soil quality. A significant increase in rice production was observed when comparing production with and without eco enzymes. The conclusion drawn from this project is that eco enzymes are an innovative organic fertilizer that enhances agricultural productivity, soil quality, and reduces reliance on synthetic chemicals sustainably. Recommendations for future work include evaluating eco enzyme compositions, studying fermentation environmental impacts, assessing soil quality impacts, production efficiency, conducting economic studies, and fostering institutional collaboration.